Developing Curug Batu Kasur through environmental conservation and community-based tourism: A qualitative study in Ciamis, Indonesia - Ari Kusumah Wardani; Ginanjar Wira Saputra; Ahmad Juliarso; Silvi Zahratun Nisa; Jeni Sriyanti (Interdisciplinary International Journal of Conservation and Culture, 2024)
Curug Batu Kasur is a small-scale nature tourism destination in Sindangkasih Village, Cikoneng District, Ciamis Regency, West Java, whose appeal rests on a clear mountain stream, a waterfall, rural scenery, and locally embedded social values. This study examines how the site can be developed through environmental conservation and community-based tourism while preserving its ecological and cultural character. A descriptive qualitative design was employed through field observation, open-ended interviews with relevant local informants, and literature review; data were interpreted through thematic comparison and triangulation. The findings indicate five interconnected development assets: relatively well-preserved natural features, a strong place identity linked to local history, community participation in tourism operations, opportunities for local economic diversification, and potential for environmental education. At the same time, limited access infrastructure, weak digital promotion, uneven managerial capacity, waste-management risks, and the absence of more systematic visitor management constrain sustainable growth. The study concludes that Curug Batu Kasur should not be developed through mass-tourism expansion, but through incremental, community-led improvements supported by collaborative governance, digital communication, conservation rules, and capacity building. This approach can strengthen local livelihoods while maintaining the natural and socio-cultural values on which the destination depends.